Closure technology of large span steel truss arch bridge with temporarily fixed edge supports - Wang Laifa; Xu Jiyang; Li Yexun; Zhou Sicheng (Nonlinear Engineering)
The Qingshuitang Bridge is a steel truss arch bridge with a very small side-to-mid span ratio, which cannot be constructed by traditional weight balancing methods and closure techniques. Applying vertical prestress at the edge support point can meet the anti-overturning requirements of cantilever construction. By adopting the hoisting process of each member, taking into account the impact of each member hoisting on the length of the closure section, as well as the effects of construction errors, installation errors, and temperature changes, the length of each member is corrected. Compared to using traditional closure method, this can make the internal forces and line shapes of the bridge closer to the design state.